Addressing the rising colorectal cancer burden in the older adult: examining modifiable risk and protective factors for comprehensive prevention strategies - He, Ke‐Jie; Liu, Zhejun; Gong, Guoyu (Frontiers in Oncology, 2025)
BackgroundColorectal cancer is one of the most prevalent and deadly cancer types worldwide. Emerging evidence suggests that high body mass index (BMI) is a significant risk factor for colorectal cancer, particularly among the older adult population. This comprehensive analysis aims to explore the complex epidemiological patterns of colorectal cancer, with a focus on the association between high BMI and disease burden in the older adult.MethodsThe study leveraged data from the Global Burden of Disease (GBD) 2021 study to examine the temporal trends, regional disparities, and the interplay of age, period, and cohort factors in shaping the global colorectal cancer landscape. Epidemiological techniques, including age-period-cohort modeling and joinpoint regression analysis, were employed to provide insights into the potential drivers of the evolving disease burden while controlling for relevant confounding factors.ResultsThe analysis revealed significant geographical disparities in the burden of colorectal cancer among the older adult population. Countries like Uruguay, Monaco, Croatia, Hungary, and Poland exhibited higher mortality and disability-adjusted life-year (DALY) rates, while regions like Bangladesh, Nepal, and much of Africa had relatively lower disease burden. These regional differences are likely attributable to variations in healthcare systems, access to screening and early detection programs, as well as differences in lifestyle behaviors and risk factor prevalence.ConclusionThe strong association between high BMI and colorectal cancer risk, particularly in the older adult population and among men, emphasizes the importance of comprehensive obesity management strategies as part of comprehensive cancer control efforts. Targeted interventions, such as community-based weight management programs and enhanced screening initiatives in high-risk regions, could help mitigate the disproportionate burden of colorectal cancer observed in countries like Monaco, Croatia, and Hungary. Ongoing research and multifaceted public health interventions are crucial to address the growing global burden of colorectal cancer and mitigate the disproportionate impact on vulnerable populations. Strengthening healthcare systems, improving access to quality cancer care, and promoting lifestyle modifications to reduce obesity and other modifiable risk factors should be prioritized to effectively combat this pressing public health challenge.